Dari Gereja, Bersama Gereja dan Untuk Gereja: Melihat Kembali Peran Penting Organisasi Pendamping Gereja Bagi Pertumbuhan Gereja - Indarto, Tommy (Veritas : Jurnal Teologi dan Pelayanan, 2023)
This article discusses parachurch (hereinafter referred to as the Organisasi Pendamping Gereja / OPG). According to Jerry White, a parachurch is all forms of spiritual ministry whose organizational structure is not under the control of the church. Reflecting on this definition, in reality, the relationship between the church and the OPG is not always harmonious, and there is often tension between the two. One of the negative issues that arise is regarding the existence of OPG. There are some churches who question the existence of the OPG and see the OPG as their rival. This article provides a perspective on the existence and important role of OPG for church growth. For this reason, this article uses a qualitative method through a literature review and is supported by the results of interviews that the author conducted. The contribution of this research is to erode the negative views held by the church regarding OPG and to encourage the church to collaborate with OPG in carrying out God's mission. From the OPG side, this article can show that the OPG should not and cannot be separated from the church.